Mother tongue : the story of the english language - Bryson, Bill (Gurgaon Penguin Random House, 1990)
With dazzling wit and astonishing insight, Bill Bryson--the acclaimed author of "The Lost Continent"--brilliantly explores the remarkable history, eccentricities, resilience and sheer fun of the English language. From the first descent of the larynx into the throat (why you can talk but your dog can't), to the fine lost art of swearing, Bryson tells the fascinating, often uproarious story of an inadequate, second-rate tongue of peasants that developed into one of the world's largest growth industries.
Keywords: English language